Diabetes Control: Is Vinegar a Promising Candidate to Help Achieve Targets? - Fahad Javaid Siddiqui MSc; Pryseley Nkouibert Assam PhD; Nurun Nisa de Souza MPH; Rehena Sultana MSc; Rinkoo Dalan FRCP; Edwin Shih-Yen Chan PhD (SAGE Publishing, 2018)
Background. Renewed interest in vinegar as a glucose-lowering agent led to several small trials in the recent past. However, none of the trials could independently provide sufficient evidence. Objectives. Our review aimed to obtain reliable estimates of effects of vinegar on short-term and long-term blood glucose control. Methods. Large bibliographic databases were searched from inception to date of search without language and publication date restrictions. All clinical trials evaluating effect of vinegar on diabetes mellitus patients were eligible. Two authors independently extracted data on fasting and 2-hour postprandial blood glucose, insulin, and HbA1c levels at the various time points. MS Excel, SAS® v9.3, and RevMan v5.3 were used for data analysis. Results. Small significant reduction in mean HbA1c was observed after 8 to 12 weeks of vinegar administration: −0.39% (95% confidence interval = −0.59, −0.18; I 2 = 0%). Other long-term outcomes favored vinegar but were not significant. Short-term outcomes showed significantly lower pooled mean difference in glucose levels at 30 minutes in the vinegar group. Readings at 60, 90, and 120 minutes were lower in the vinegar group but not statistically significant. Adverse effects profile also favored the vinegar group. Conclusions. It is worthwhile to carry out carefully planned large trails to determine the efficacy and effectiveness of vinegar as an adjunct treatment modality.